System of Continuous Agricultural Education in Precarpathia (Late XIX - early XX centuries) - Bilavych , Halyna (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
Ukrainian public communities have important achievements in development of the system of continuous agricultural education in Precarpathia - Ukrainian Pedagogical Society “Ridna Shkola”, “Prosvita”, “Silskyi Hospodar”, the Union of Ukrainians and others. In the late XIX - early XX centuries, they held important educational work among adults, organized various forms of training - courses, professional-complementary schools, agricultural schools, high schools, colleges, courses, public universities etc. All this contributed to increasing of economic culture of the Ukrainian land. Formation of economic culture of children and adults in Precarpathia had its own characteristics, mainly associated with the economic, social, historical, climatic, cultural and educational conditions of life and activities. The system of continuous agricultural education included some educational institutions such as courses, vocational schools, which performed various levels of training. Agricultural schools became an important area of lifelong education. Let us consider, for example, the activities of two schools - one of the first established societies “Enlightenment” in the Precarpathia - schools in Mylovanya (Tlumachchyna) and Starokosivska, which was founded in 1942 during the German occupation. Thus, on condition of the absence of state Ukrainian professional schools in the late XIX - early XX centuries civil societies created a system of continuous agricultural education which was aimed at improving the economic culture of young people and adults